Precut Papillotomy versus EUS-Guided Rendezvous in Difficult Biliary Cannulation for Malignant Distal Biliary Obstruction: Time to Think Outside the Box? - Ancil, Sanish; Shah, Jimil; Jearth, Vaneet (Journal of Digestive Endoscopy, 2025)
The rates of difficult biliary cannulation (DBC) while attempting endoscopic retrograde cholangiopancreatography (ERCP) go up to 11% even in experienced hands. Salvage techniques such as the double guidewire technique, precut papillotomy (PCP), and transpancreatic precut papillotomy are beneficial for patients with DBC. Notably, with the advent of endoscopic ultrasound (EUS), different procedures, such as the EUS rendezvous technique (RV) and EUS-guided transmural biliary drainage, have come into play. In this news and views, we will review a recently published open-label, parallel-group randomized clinical trial that compared PCP and EUS-RV as therapeutic options for DBC in patients with malignant distal biliary obstruction. With a focus on multidisciplinary decision-making, the practicality of employing EUS-RV in malignant disease and the evidence-based approach according to the underlying disease requiring biliary drainage (benign vs. malignant) will be covered.
Keywords: ERCP; EUS; difficult biliary cannulation; biliary drainage